2018
DOI: 10.1159/000492438
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Alport Syndrome: Lessons from the Pediatric Ward

Abstract: Background: Alport syndrome is a rare inheritable kidney disease frequently leading to end-stage kidney disease in young adults. Patients could benefit from early recognition of the disease. In several children with Alport syndrome, a parent was noticed to have renal symptoms attributed to another renal disease. Aim: To review the renal history of the closest family members of a cohort of pediatric patients with genetically proven Alport syndrome. Methods: The medical records of all children with genetically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
5
0
3
Order By: Relevance
“…Therefore, this analysis finally included 26 eligible articles with 148 patients (Figure 1) [7,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. The respective characteristics of included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this analysis finally included 26 eligible articles with 148 patients (Figure 1) [7,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. The respective characteristics of included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that most pediatric patients diagnosed with AS have atypical clinical manifestations from their parents and it is di cult to detect AS patients in time (Vos et al, 2018); therefore, nephrologists should focus on the emergence of patients with unexplained hematuria, proteinuria, or renal failure and determine whether there is a positive family history of kidney disease. Patients with XLAS are not uncommon in clinical practice, with around one case of X-linked AS patients in every 50,000 newborns (Vos et al, 2018). There is still no cure and the prognosis is poor and often progresses to endstage renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…El síndrome de Alport es la segunda causa monogénica más común de enfermedad renal crónica (ERC) después de la poliquistosis renal autosómica dominante (14) . Genéticamente, en estudios de poblaciones se encuentra predominio en mutaciones COL4A5 en relación a COL4A3 y COL4A4, respectivamente (22) . La clínica primordialmente se caracteriza por hematuria persistente, pero de acuerdo al sexo es posible encontrar predominio de hematuria microscópica en todos los casos masculinos y en las pacientes femeninas se caracteriza aproximadamente el 98% por hematuria y el 73 % hematuria y proteinuria.…”
Section: Desarrollo Y Discusiónunclassified